The Potential of Hydrolysate from Rabbit Meat Protein as an Angiotensin Converting Enzyme Inhibitor - Edy Permadi; Jamhari Jamhari; Edi Suryanto; Zaenal Bachruddin; Yuny Erwanto (Buletin Peternakan, 2019)
This research aimed to investigate the rabbit meat hydrolysate potential as an angiotensin-converting enzyme (ACE) inhibitor. Indonesian local rabbit meats were used in this study. The research was conducted in Department of Animal Product Technology, Faculty of Animal Science, Universitas Gadjah Mada, from August 2016 to February 2017. The local rabbit meats were hydrolyzed by pepsin, trypsin, and pancreatic. The obtained hydrolysates were then analyzed to identify the water-soluble protein content. The molecular weight of the hydrolysates were also confirmed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The ACE inhibitory properties of the hydrolysates were analyzed in vitro. The results showed that pepsin, trypsin, and pancreatic hydrolysis showed a significant effect on the water-soluble protein content of rabbit meat (p<0.05). The water-soluble protein of rabbit meat hydrolysed by pepsin, trypsin, and pancreatic were 9.41, 7.66, and 9.75 mg/mL respectively. The molecular weight of the rabbit meat hydrolysate were increased from 10 to 43 kDa; 17 to 43 kDa; and 10 to 43 kDa, after hydrolysed by by pepsin, trypsin, and pancreatic respectively. Furthermore, the ACE inhibitory properties ) of the hydrolysed rabbit meat by pepsin, trypsin, and pancreatic were 439, 170, and 380 μg/mL, respectively. The rabbit meat hydrolysate showed a potential to be ACE inhibitor after hydrolyzed with pepsin, trypsin and pancreatic. Moreover, it also showed a promising potential to be used as bioactive components in different pharmaceutical applications. The highest ACE inhibitory capability was showed on trypsin hydrolysis with the total of 65.45% and 170 μg/mL ACE inhibition